2003
DOI: 10.1046/j.1365-2249.2003.02225.x
|View full text |Cite
|
Sign up to set email alerts
|

Pimecrolimus does not affect the differentiation, maturation and function of human monocyte-derived dendritic cells, in contrast to corticosteroids

Abstract: SUMMARYClinically, corticosteroids (CS) are among the first line drugs in the therapy of autoimmune and allergic diseases and potently inhibit the activation of immune cells. However, due to their pleiotropic mode of action, the prolonged use of CS is generally associated with a range of undesirable side-effects. In this study, we compared the activity of pimecrolimus, a novel immunomodulatory drug for the treatment of inflammatory skin disorders, and the CS dexamethasone (Dex) and beta-methasone-valerate ( b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 50 publications
(61 reference statements)
4
40
0
Order By: Relevance
“…This inhibitory effect of dexamethasone on the iNOS/NO pathway in DC, apart from a known effect on T cells and keratinocytes, may account for some of the antiinflammatory properties of topical corticosteroids observed in inflammatory skin conditions (38)(39)(40)(41)(42) . A more pronounced inhibition of dexamethasone in the process of activation of DC by allergens, both during sensitization and the afferent phase of ACD elicitation, can sustain why medium/potent topical and systemic steroids are more effective in the treatment of ACD than the recently commercialized topical immunosuppressors, tacrolimus and pimecrolimus, which act through molecular mechanisms similar to cyclosporin A and sirolimus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibitory effect of dexamethasone on the iNOS/NO pathway in DC, apart from a known effect on T cells and keratinocytes, may account for some of the antiinflammatory properties of topical corticosteroids observed in inflammatory skin conditions (38)(39)(40)(41)(42) . A more pronounced inhibition of dexamethasone in the process of activation of DC by allergens, both during sensitization and the afferent phase of ACD elicitation, can sustain why medium/potent topical and systemic steroids are more effective in the treatment of ACD than the recently commercialized topical immunosuppressors, tacrolimus and pimecrolimus, which act through molecular mechanisms similar to cyclosporin A and sirolimus.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, recent reports showed that pimecrolimus, a nonsteroid calcineurin inhibitor, has little effect on DC differentiation, maturation and immune function, in contrast to corticosteroids that showed pronounced effects on DC (38)(39)(40)(41) . When compared with calcineurin inhibitors, namely cyclosporin A and tacrolimus, corticosteroids have a unique and profound inhibitory effect on the generation and function of DC (42) .…”
Section: Inos Expression By Skin Sensitizers 235mentioning
confidence: 99%
“…More specifically, in an in vitro study of mononuclear cells obtained from healthy volunteers, corticosteroids have been shown to cause apoptosis of monocyte-derived DC (M-DC) precursors and inhibit the expression of DC-specific antigens such as CD1a, CD40, and CD80. In addition, corticosteroids inhibit the expression of critical DC factors such as CD83 and CD86, the synthesis of IL-12p70, and the ability of DCs to activate primary CD4+ T cell proliferation [24]. Topical corticosteroids also have an adverse effect on IL-12 expression in LCs/DCs.…”
Section: Topical Treatments For Admentioning
confidence: 99%
“…Topical short-term treatment of even low potency corticosteroids eliminates LCs in the skin by inducing apoptosis. Experimental data show that after stopping application of topical corticosteroids, repopulation of the epidermis with LCs takes weeks [24,25,26,27]. …”
Section: Topical Treatments For Admentioning
confidence: 99%
“…19,20 It does not interfere with the differentiation, maturation, and function of cells involved in immunosurveillance, specifically dendritic cells/Langerhans cells. [21][22][23][24][25] Pimecrolimus cream has demonstrated a much lower potential for percutaneous absorption than TCSs, because of its higher molecular weight and lipophilicity. 26,27 Unlike TCSs, it does not cause skin atrophy and does not affect the hypothalamic-pituitary-adrenal axis.…”
mentioning
confidence: 99%